The experience of social adaptation problem solving in the Donbass region of Ukraine - Sergei Ivanov; Vyacheslav Koval; Alexander Lyakh (European Regional Science Association (ERSA), 1998)
Old industrial regions such as Donbass region in Ukraine, require intensive restructurization to facilitate them full participation in the economic life of the country on equal rights as other regions of Ukraine as well as to ensure proper life conditions to the inhabitants of these regions, in which huge part of the country's population concentrate. Now this problem is solving mostly by means of technical closing of unprofitable enterprises. Especially it concerns the coal mine industry. This is a right way assuming that exists a real program of restructuring which includes not only the main steps of it but also the evaluation of all the process along with estimation of social transition cost. But because of absence of a sober policy in this process and poor information dissemination the government gets into a much more complicated problem - the growth of social unprotection, unsettleness and pauperization of a huge layer of the active able-bodied population. Such social cost of ungrounded restructurization is difficult to be accepted in modern state. In order to facilitate process of adaptation of population to new conditions the International Renaissance Foundation with Polish partners have jointly launched a project aimed at the development and dissemination of a strategy and methods of economic and social problems solving which connected to the process of restructurization of old industrial regions in countries in transition. The main topics of the project: - Regional community member's awareness. - General education, training the present and future managerial cadre, re-qualification and socio-professional reconversion. - Role of information in the process of restructurization. - Transformation the old and setting up new enterprises. - Creation and improvement of the instruments and the institutions of regional restructurization. - Conducting a forum of public dialogue. There are steps that have been already done on the way of project implementation: - Quantitative investigations - sociological analysis of four sites in Donetsk region mostly populated with coal miner's families. - Qualitative investigations on the above mentioned topics. - Three workshops conducted in Donetsk region (sities of Donetsk, Mekeevka and Stakhanov). - One workshop conducted in Gliwice (Poland). All the workshops were dedicated to investigation of the approaches to the creation of a decision making strategy which would help to solve problems of industrial restructurization, rebuilding of country's economy, and economic and social consequences of this processes. Along with the project implementation there have been established the Agency for Regional Development in Donetsk as an institution that is aimed to help the economic reforms promotion and practical implementation of the steps on structural rebuilding in the Donetsk region. In addition, two centers for Social Adaptation of Coal Miners were set in the sites of closed coal mines in Donetsk with the help of the International Renaissance Foundation. The future development of this project assumes to widen the circle of its participants including representatives from Nord-Rhein Westphalen (Germany) and Nord-Pas-de-Calais (France). The overall objective of the new phase of it is to use the combined experience of the project partners in order to develop and implement strategies which effectively address the economic problems caused by the decline in the coal mine industry. Key words: restructurization, social adaptation, decision making strategy.
Keywords: 330